"Mind full or mindful" – can mere cognitive busyness lead to compliance similar to an emotional seesaw?. (2nd October 2019) - Kaczmarek, Magdalena C.; Steffens, Melanie C.
ABSTRACT: The emotional seesaw phenomenon (ESP) is a social-influence technique in which a person experiences a certain emotion, where the external stimulus that evoked the emotion suddenly disappears. Large effects on compliance and impaired cognitive functioning were reported after ESPs. The present research (total N = 163) tests a generalization of this phenomenon: whether mere cognitive busyness leads to similar effects by provoking an inner focus. Two experiments closely modeled after previous ESP experiments supported this reasoning: a simple expectancy violation (Experiment 1) and cognitive load (Experiment 2) caused a comparable pattern of results as the ESP. Experiment 3 demonstrated that also the ESP fostered an inner focus and consequently compliant behavior. We discuss mechanisms underlying social-influence techniques.